PENGARUH PIJAT BAYI TERHADAP PERTUMBUHAN BAYI - Wiwi Sartika; Sara Herlina; Siti Qomariah (Poltekkes Kemenkes Bandung, 2023)
Infancy is a stage where growth and development are very fast, from the baby's birth until he is one year old. The baby's developmental age is divided into 2, namely, neonates from birth to 28 days old and babies from 29 days to 12 months. This study aims to see the effect of infant massage on growth in infants. This research method uses a pre-experimental design with a one-group pre-test and post-test research approach. The sampling technique used purposive sampling. There were 26 samples in the study between the ages of 0-12 months. Data analysis was used univariately and bivariate using the Wilcoxon pre-test -post-test. Obtained a p-value of 0.025 (p <0.05) means that Ha is accepted and Ho is rejected. It can be concluded that there is an influence between Baby Massage on growth in infants in the Simpang Baru Health Center work area. It is recommended for mothers who have babies to be able to massage the baby as often as possible because the mother's touch can increase the baby's growth.